Influence of deformations on the reentrant conductance feature in semiconducting nanowires - Cunha, Iann [UNESP]; Villegas-Lelovsky, Leonardo [UNESP]; Castelano, Leonardo Kleber [UNESP] (Elsevier, 2022)
Helical states can be measured through the observation of the reentrant behavior, which is a dip in the conductance probed in semiconducting nanowires (NWs) with strong spin-orbit coupling (SOC) under the presence of an external perpendicular magnetic field. We investigate the effects of deformation in the electronic transport in NWs considering the coupling between different transverse modes. Within this approach, we show that the dip in the conductance is affected by the presence of a local constriction in the NW. Moreover, we find that the reentrant feature in the conductance can appear in NWs containing a local expansion of its radius, even in the absence of SOC and magnetic field. This result demonstrates that the reentrant feature can be found within certain conditions that differ from those expected to probe helical states. Therefore, the reentrant feature cannot always be associated with the observation of helical states. Furthermore, we develop a numerical approach to calculate transport properties, which can include the deformation and the coupling among several scattering channels.
Keywords: Deformations; Helical states; Majorana bound states; Nanowires; Reentrant feature; Spin-orbit